The history of seismology and historical seismicity in Algeria: an overview - Bezzeghoud, Mourad (2022)
Algeria is one of the most seismically active areas along the Nubia-Eurasia convergent plates boundary. It is well known that the instrumental records of seismic events are incomplete because of inadequate instrumentation and the poor coverage of seismogenic areas from 1900 until the installation in 1992 of the Algerian Telemetered Seismological Network. The available catalogues of the seismicity of Algeria, including several published research papers on the same topic, reported numerous destructive earthquakes striking several regions, particularly along the coast [Oran, Mascara, Chlef (Former Orléansville and El Asnam), Tipasa-Chenoua, Algiers, Zemmouri, Constantine, Béjaia, Djidjelli (5.9 < M < 7.3; IX < Io < X]. This seismicity is the result of the collision between the Nubia and Eurasian plates and is located within the Algerian Tell Atlas. To properly study the seismicity of Algeria, we must consider three periods in relation to the installation of the seismic instrumentation over the Algerian territory: (1) the pre-1910 period with the first published seismic catalogues, (2) the post-1910 period with the beginning of the instrumental seismicity and, finally, (3) the post-1980 period with the installation of the Algerian Teleseismic Network in 1990 and its upgrade following the Zemmouri earthquake of May 21st 2003.